Inflammatory Markers Combined With Metalloproteinase-9, Neopterin, and S100B Concentrations May Indicate the Pathogenesis of Central Nervous System Diseases in Children. (August 2022) - Lubarski, Karol; Mania, Anna; Małecki, Paweł; Mazur-Melewska, Katarzyna; Figlerowicz, Magdalena
The identification of central nervous system inflammation etiology leads to adjusted therapy. We analyzed the potential inflammatory and neuro-axonal damage markers in children. Our target was to correlate the findings with a disease's course or a sequalae risk and assess their clinical usefulness. The study included 96 children with symptoms of central nervous system inflammation who underwent diagnostics. The research group involved 24 children with autoimmune disorders and 31 with neuroinfection. The control group included patients with both etiologies excluded. We analyzed the results of routine laboratory tests together with chosen serum (neopterin, interleukin [IL]-1β, IL-6) and CSF (metalloproteinase [MMP]-9, S100B protein) markers. In the whole cohort, CSF MMP-9 correlated with CSF cytosis and serum IL-6 and CRP. In the undivided neuroinflammatory group, CSF S100B correlated with serum IL-6 and IgM concentrations. CSF cytosis was associated with CSF MMP-9 and serum neopterin levels. Among the infective patients, IL-6 was linked with increased CSF MMP-9. We conclude that astroglial protein S100B, neopterin, and cytokine concentrations may enable predicting long-term consequences, whereas CSF MMP-9 concentration may reflect the actual central nervous system injury regardless of etiology.